Promotion of Fluorescence upon Binding of Colchicine to Tubulin - Bhattacharyya, B. (1974)
Colchicine, which does not fluoresce in aqueous media and organic solvents, exhibits marked fluorescence on combination with brain tubulin, with a corrected excitation maximum at 362 nm, an emission maximum at 435 nm, and a quantum yield of about 0.03. From fluorescence measurements it was found that rat brain tubulin binds 0.83 moles of colchicine per dimer (molecular weight 110,000) with an association constant of 3.2 μM(-1) at pH 7.0 and 37°. These results are in excellent agreement with those obtained with the binding of [(3)H]-colchicine. The enthalpy of binding is 10 kcal/mole, with an entropy change of 62 entropy units. The fluorescence can be ascribed to the tropolone moiety. However, the A ring of colchicine is also involved in binding. Denaturing agents abolish fluorescence, whereas podophyllotoxin, another antimitotic agent, decreases fluorescence competitively. Fluorescence is a convenient method for determining the binding of colchicine to tubulin that does not require the separation of free colchicine from bound colchicine and yields values for physical and biochemical parameters that are in excellent agreement with those obtained from the binding of [(3)H]colchicine.